High Dose Consensus Interferon in Nonresponders to Interferon Alpha-2B and Ribavirin with Chronic Hepatitis C - David N Moskovitz; Pooma Manoharan; E Jenny Heathcote (Canadian Journal of Gastroenterology)
OBJECTIVES: Approximately 60% of patients with chronic hepatitis C treated with a combination of interferon (IFN) alpha-2b and ribavirin are nonresponders. The purpose of the present study was to evaluate the efficacy of treatment with high dose consensus IFN (CIFN) (15 µg/day) in nonresponders.